2017
DOI: 10.3390/su9061000
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Milk Composition at Different Stages of Lactation from a Small Herd of Nguni, Boer, and Non-Descript Goats Raised in an Extensive Production System

Abstract: This study was conducted to evaluate the yield and composition of milk from 30 indigenous South African goats of different genotypes, namely Nguni, Boer, and non-descript, reared under a free-ranging system. Milk yield and composition (milk fat, protein, lactose, solid non-fat, and minerals) from Nguni (10), Boer (10) and non-descript (10) goats were measured and analysed per week at each stage of lactation. Results showed that Nguni goats produced (1.2 ± 0.09, 1.3 ± 0.11 and 1.2 ± 0.07 L per day) more milk (p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
4
13
2
Order By: Relevance
“…This is contrary to our finding where medium milk yield did not depress milk components in mixed-breed goats. Our results, however, are in line with the results of Idamokoro et al [ 33 ] who found no correlation between milk yield and milk compositions for non-descript grazing goats.…”
Section: Discussionsupporting
confidence: 93%
“…This is contrary to our finding where medium milk yield did not depress milk components in mixed-breed goats. Our results, however, are in line with the results of Idamokoro et al [ 33 ] who found no correlation between milk yield and milk compositions for non-descript grazing goats.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, there were some reports related to variations of fat content (Pridalová et al, 2008;Strzałkowska et al, 2010;Králíčková et al, 2013;Klir et al, 2015). When the results of this study were compared with previous studies, it can be said that they were lower than the values reported by some researchers (Klir et al, 2015;Kučević et al, 2016;Idamokoro et al, 2017). Fat composition of Honamlı goat milk may be associated with feeding regime, because it's a fact that fat and protein content of milk is influenced mostly by feeding (Toledo-Alonzo, 2003;Goetsch et al, 2011).…”
Section: Discussioncontrasting
confidence: 55%
“…While this value was compatible with the other studies (Sengonca et al;2003;Ata, 2007) related to native goats breeds of Turkey; Simsek et al ( 2006) found higher values(0.900 kg.) than the present study.Additionally, there were variability of daily milk yield reports for different goat breeds for numerous authors (Mestawet et al, 2012;Králíčková et al, 2013;El-Tarabany et al 2016;Idamokoro et al, 2017). The milk yield value of Honamlı goat might be associated with genotype and especially inadequacy of nutritional imbalance because of extensive rearing system.…”
Section: Discussionmentioning
confidence: 99%
“…While this value was compatible with the other studies (Sengonca et al;Ata, 2007) related to native goats breeds of Turkey; Simsek et al ( 2006) found higher values(0.900 kg.) than the present study.Additionally, there were variability of daily milk yield reports for different goat breeds for numerous authors (Mestawet et al, 2012;Králíčková et al, 2013;El-Tarabany et al 2016;Idamokoro et al, 2017). The milk yield value of Honamlı goat might be associated with genotype and especially inadequacy of nutritional imbalance because of extensive rearing system.…”
Section: Discussionmentioning
confidence: 99%